Base hydrolysis and aquation of trans-methyl-substituted acidopenta-amminecobalt(III) complexes - Benzo, Fabián (1996)
Base hydrolysis and aquation of trans-[Co(NH₃)₄(NH₂CH₃)X]²⁺ (where X = Cl, Br and NO3) complexes are reported. Both types of reactions are four to eight times faster than the corresponding reactions for [Co(NH3)5X]2+ complexes. The positive activation entropies of the base hydrolysis for all the studied trans-[Co(NH₃)₄(NH₂CH₃)X]²⁺ ions and the stereochemistry of the hydroxo products are indicative of a dissociative conjugate base, Dcb, mechanism. The steric course of the base hydrolysis differs significantly from that of the parent penta-ammines. For the aquation reactions, the activation enthalpies of the trans-methylamine and penta-ammine complexes are similar, while the activation entropies are more positive (or less negative) for the former. These results are interpreted in terms of an Id mechanism.